Instilling 21st Century Skills in Early Childhood Through STEAM Learning at Paud Mutiara Bunda Gandusari - rina insani setyowati (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
To face various challenges in this changing period, 21st century skills are needed. However, in the implementation of learning in institutions there are still problems, and this can be seen in the achievement of children's development which is still low, such as the development of critical thinking that is not optimal, limited creativity, children's language. both in communication and listening to children are still lacking, and collaboration has not been able to work well together. This problem arises because educators provide little opportunity for children to explore their abilities with various limitations, including a lack of variety of play activities, so that 21st century skills cannot be mastered by children. To overcome this problem, STEAM learning is used which is one of the lessons that can be applied at school or when children play at home. With STEAM, children will get used to being able to develop new knowledge in a fun way, and it is hoped that one day they will be able to provide solutions to the problems that exist in the world. The results of observations in the Mutiara Bunda Play Group for 21st century learning have begun but are not optimal, so students have not fully mastered these skills. Therefore, from the existing problems, educators use STEAM-based learning. The research method used is descriptive qualitative research to see the prospects of teachers in understanding and implementing the STEAM method by asking several questions, as well as with additional research subjects 12 children aged 3-4 years in Paud Mutiara Bunda Gandusari. Collecting data with observation and documentation techniques, which were analyzed qualitatively to determine the achievement of children's development. The results showed that using STEAM learning can instill 21st century skills in early childhood.